How Do Interpersonal Conflict Management of Principal Develop Teacher Pedagogical Competence: Literature Review - Zelda Amini (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2022)
Principals and teachers are the most important actors in school. Teacher pedagogical competence is very important to develop teacher professionalism. And also, principal performance has a substantial impact on teacher pedagogical competence. This can be seen in how the principal handles interpersonal conflicts. The objectives of this paper is to describe and find out the link between a teacher's pedagogical and interpersonal conflict management of principals. The result of this study is the way the principal handles conflicts that occur in schools can increase harmony between school members, especially teachers. A harmonious relationship between teachers will be created by the principal who can handle conflict in their school.